KEJADIAN DERAJAT LUKA DIABETES TIDAK BERHUBUNGAN DENGAN NILAI RISIKO DIABETIC FOOT ULCER - Risma Anggraeni Yuliastuti; Megah Andriany; Eka Putri Y. (Poltekkes Kemenkes Jakarta III, 2017)
The highest diabetic complication percentage is neuropathy (54%) causing diabetic foot ulcer (DFU). The study aimed to know the relationship between diabetic foot ulcer risk levels with diabetic ulcer severity levels. Scope of the study was diabetic wound care, particularly on legs mostly experienced by diabetic patients. The method used was descriptive correlation with cross sectional design. Sampling method was non probability with purposive sampling. Respondent number was 16 persons with inclusion criteria was diabetic patients with ulcer in one leg and no ulcer on another side in the second visitation to a diabetic clinic in Bekasi,Indonesia and agreed to be involved in the study. DFU risk level instrument modified from Diabetes Foot Screening and Risk Stratification Form of New Zealand Society for Study of Diabetes (NZSSD) to measure the DFU degree on legs with no ulcer. Another tool was to measure severity level of legs with ulcer according to Wagner. Data analysis used Kendall’s tau with 0.05 of significance level. The result shows there is no relationship between DFU risk levels with severity degree of diabetic ulcers. From the study, we can conclude that nurses do not need provide specific DFU prevention based on diabetic ulcer severity grade.